PENGELOLAAN KAWASAN KONSERVASI HUTAN MANGROVE DAN BEKANTAN (NASALIS LARVATUS) (KKMB) DI KOTA TARAKAN - Supardi (INTAN Jurnal Penelitian Tambang, 2019)
Mangrove and Bekantan (Nasalis larvatus) conservation areas (KKMB) in Tarakan City is a mangrove city forest area that in the development stage sepecially for Bekantan population and mangrove ecosystem at large. With an area of about 22 hectares and at least 11 protected animal species includes Bekantan, the KKMB has become iconic tourism attraction. This not only of the rarity of the attraction but also because of this kind of venue is the only one in the world. This research aimed to find out the management, the uniqueness and the obstacles faced in managing KKMB. The methods used are interview, observation and literature study. The data obtained are compiled, processed, and analyzed with descriptive qualitative analysis methods, by providing an overview of the situation or events and phenomena in the field. From the study, we could understand that the KKMB is manage by the Tarakan City Tourism Office. The retribution came from KKMB are deposited to the Tarakan City Revenue Service. Furthermore, the uniqueness of KKMB that attracts tourists to visit due to its strategic location in the middle of the urban area adjacent to the shopping centers, settlements, fishponds, companies, and access roads / ports. Two main attraction of the KKMB are bekantan (proboscis mongkey) endemic to Borneo and The red mangrove (Rhizophoraa Apiculata). Last, the problem faced by the management of KKMB are no clear organizational structre and waste management that come from tides, domestic waste, and visitors. Also in KKMB there is no clear organizational structure.